Mindi (Melia azedarach Linn.) Growth and Soybean (Glycine max (L.) Merril) Production of Agroforestry Pattern on The Sour Land PERTUMBUHAN MINDI (Melia azedarach LINN.) DAN PRODUKSI KEDELAI (Glycine max (L.) MERRIL) DENGAN POLA AGROFORESTRI .... - Alisa Maulina Jauhari; Nurheni Wijayanto; Omo Rusdiana (Departemen Silvikultur, Fakultas Kehutanan dan Lingkungan, Institut Pertanian Bogor (IPB), 2016)
A Survey in West Java shows that Mindi (Melia azederach Linn.) is frequently found on the community forest lands as part of a mixed cropping system. These community forest lands have a potential to support food security. Soybean is an important food crop as source of protein in Indonesian. This study aimed to observe the growth of Mindi and soybean in an agroforestry system. This study used a split plot design which consists of two factors. The main factors was Mindi which planted using shade and without shade and the second factors are soybean variety (Argomulyo, Anjasmoro, Grobogan, and Wilis) using four replication. The results showed that differences of Mindi cropping method did not significantly affect the Mindi growth (height and diameter) which has been observed for three months. Wilis had the highest survival rate than others varieties. Both factor shade and varieties giving a very significant effect on the kedelai height at the 3-7 MST age. In addition, it's also very significantly affected the number of leaves trifoleat at the age of 3, 4, and 5 MST. Soybean production in Mindi agroforestry system gaves the higher yield than monoculture system at three months age.Key words: Agroforestry, mindi, soybeans, shade, variety.